PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI OPERASIONAL PADA PT. BERLIAN JASA TERMINAL INDONESIA - Teguh Prihandoko; Pompong B Setiadi; Sri Rahayu (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
This study aims to determine how much influence training and work motivation partially or simultaneously on the performance of employees of PT Berlian Jasa Terminal Indonesia. The method that will be used is explanatory research and hypothesis testing. With the survey technique, the questionnaire was distributed with a Likert scale. The determination technique uses saturated sampling with 100 respondents mainly employees who work in the operational division. The data analysis techniques used were descriptive analysis and inferential statistical analysis, namely: 1. Validity and Reliability Test, 2. Multiple Regression Analysis, 3. Coefficient of Determination Analysis (R2), 4. Hypothesis Testing with Partial Test (t test) and Simultaneous Test ( F test) The results of the test and analysis are as follows:1. There is a positive and significant effect between training on employee performance, with an R Square of 0.489 or 48.9%. Hypothesis test p value 0.000 <0.05,2. There is a positive and significant effect between motivation on employee performance, with an R Square of 0.470 or 47.0%. Hypothesis test p value 0.000 <0.05.and 3. There is a positive and significant effect between training and motivation simultaneously on employee performance, with an R Square of 0.591 or 59,1%. Hypothesis test p value 0.000 <0.05.